Analysis of the Digital Transformation of Legal Services and the Role of Policy Brokers in KOREA through the Advocacy Coalition Framework - Han, Ji-won; Jun Park, Hyung (Indonesian Association for Public Administration, 2025)
This study examines the intersection of traditional legal services and technological innovation by employing an Advocacy Coalition Framework (ACF). Our primary focus is on the protracted dispute between the Korean Bar Association and the LawTalk legal service platform. Emerging legal service platforms, such as LawTalk, have disrupted conventional legal frameworks, resulting in substantial regulatory and ethical disputes as digital transformation accelerates, as was particularly evident during the COVID-19 pandemic. This research examines the development of this conflict over a nine-year period, utilizing the ACF to analyze the roles and influence of the various advocacy coalitions involved. Our findings underscore the dual challenge of integrating new technologies within the rigid structures of traditional legal systems. The conflict, which is primarily focused on the legality and ethical implications of LawTalk's business model, is indicative of more general tensions between innovation and regulation. The critical role of neutral intermediaries in balancing stakeholder interests and adapting policies to technological advancements is underscored by the resolution process, which is mediated by policy brokers such as the Ministry of Justice. The case of LawTalk not only elucidates the intricacies of policy change in the digital era, but also provides valuable insights into the management of sectoral transformations that adhere to both established regulatory norms and innovation. This study elucidates the necessity of ongoing dialogue and adaptation in policy frameworks to accommodate technological change, thereby contributing to our understanding of policy dynamics in the legal domain.